The Influence Of Brand Image And Advertising On Social Media On Consumer Purchase Decisions On Emina Products (Case Study Of Students In Bandar Lampung) - Siti Mahmudah; Defia Riski Anggarini (Jurnal Ekonomi, 2024)
This research aims to examine the influence of brand image on purchasing decisions of Emina products and the impact of social media advertising on consumer purchasing decisions. The background of this study is the increasing competition in the cosmetics industry, which necessitates companies to build a strong brand image and utilize social media as an effective promotional tool. This quantitative study employed a purposive sampling technique with a sample size of 115 Emina product consumers in Bandar Lampung. The independent t-test results indicate that brand image has a partially positive and significant effect on Emina products among Bandar Lampung students. Furthermore, the simultaneous F-test results show that there is a significant influence between the brand image and social media advertising variables on Emina products among Bandar Lampung students. Overall, this research shows that Brand Image has a positive effect on purchasing decisions and Social Media Advertising has a positive impact on purchasing decisions.